Implementation of Article 36 of Law Number 42 of 1999 concerning Fiduciary Security Regarding the Imposition of Criminal Sanctions for the Transfer of Fiduciary Collateral Objects - Suhardi; Hambali Yusuf; Abdul Latif Mahfuz; Habiburrahman (NEGREI: Academic Journal of Law and Governance, 2025)
Many fiduciary grantors, such as individual debtors, are unaware that transferring fiduciary collateral objects without written permission constitutes a criminal offense. They often perceive the collateral as entirely their own property. Such criminal acts are frequently committed without malicious intent (mens rea), which has sparked debates regarding their treatment under criminal law. This study examines the implementation of Article 36 of Law Number 42 of 1999 concerning Fiduciary Security, particularly in relation to the imposition of criminal sanctions for the transfer of fiduciary collateral objects without the written consent of the fiduciary recipient. The primary focus of this research is to assess the effectiveness of the application of this criminal provision in practice, as well as to identify both legal and non-legal obstacles in the enforcement process. This research uses a normative juridical method with a qualitative approach, employing both primary and secondary legal materials. The findings indicate that Article 36 of the Fiduciary Security Law is no longer relevant, and that the imposition of criminal sanctions for the transfer of fiduciary collateral objects does not yet reflect a sense of justice. Criminal sanctions against fiduciary grantors who transfer fiduciary collateral are regulated under Article 36 of Law No. 42 of 1999; however, third parties (i.e., receivers or buyers of the collateral) are not regulated under this law. As a result, fiduciary recipients often feel disadvantaged. However, with the verdict of the Kebumen District Court Number 50/Pid.B/2019/PN.Kbm dated April 11, 2019, the perpetrator of the offense of receiving fiduciary collateral objects (i.e., fencing) can now be prosecuted under Article 480 of the Indonesian Criminal Code (KUHP).